Konsumsi Makanan Tinggi Garam Berhubungan dengan Kejadian Double Burden of Malnutrition pada Remaja Usia 16-18 Tahun di DKI Jakarta: High Salt Intake Associated with Double Burden of Malnutrition in Adolescent Aged 16-18 Years in DKI Jakarta - Zulfa Syauqiah; Utami Wahyuningsih; Firlia Ayu Arini (Universitas Airlangga, 2025)
Background: Double Burden of Malnutrition (DBM) refers to the coexistence of two forms of malnutrition within the same individual. DKI Jakarta is among the provinces reporting a relatively low prevalence of normal nutritional status among adolescents at the national level. The occurrence of DBM is multifactorial and may be influenced by sociodemographic characteristics (including household size, parental occupation, and parental educational attainment), dietary patterns, the consumption of high-risk foods, and physical activity. Objectives: This study aimed to examine the factors associated with the occurrence of the double burden of malnutrition among adolescents aged 16-18 years in DKI Jakarta. Methods: A total of 528 adolescents residing in DKI Jakarta were included, and a cross-sectional study design was employed using secondary data from the 2023 Indonesian Health Survey (Survei Kesehatan Indonesia, SKI). Multivariate logistic regression analysis was conducted to identify factors associated with the occurrence of DBM. Results: Among the 528 adolescents, 0.8% were identified as experiencing DBM, comprising stunting-thinness (0.6%) and stunting-overweight (0.2%). Multivariate analysis revealed that the consumption of foods high in salt was significantly associated with DBM (p-value=0.024; OR=0.058; 95%CI=0.005-0.686). However, the low prevalence of DBM represents a study limitation, indicating that future studies with larger sample sizes are required. Conclusions: The findings indicate that adolescents who frequently consume salty foods had lower odds of experiencing DBM compared to those who rarely consume such foods.